초전도 전류 특성 - 이상헌(Sang-Heon Lee) (전기학회 논문지 P권, 58(4), 2009)
As a kind of high Tc superconductor application technique, a study on the development of energy storage device system using BiPbSrCaCuO superconductor was performed. Chemical melt process was developed to gabricate the high magnetization superconductor which is needed to develop the energy saving system and the effect of various process variable on the superconducting properties of the specimens were tested and analyzed. Magnetochemical interactions between superconductor and permanent magnet was also experimented.